Teaching gender and sexuality in the wake of the Must Fall Movements: Mutual disruption through the lens of critical pedagogy. - Andrews, G. (My University, 2020)
The recent Must Fall movements shone a light on how South African universities are exclusionary spaces in many respects. In addition to the focus on racial, financial, and epistemological exclusions, the movements also highlighted how gender and sexual minorities are marginalised in university curricula and spaces. In the wake of these movements, I taught a range of courses dealing with gender and sexuality to pre-service teachers at a South African university. Using an autoethnographic approach, I recount some of the challenges I faced in teaching subject matter that many South Africans consider controversial. Students often relied on simplistic discourses of culture and religion to voice resistance to my courses and to "disrupt" my classes, while the subject matter simultaneously disrupted their deeply held concepts of identity. These moments of disruption from students, while largely intended as resistance, offered considerable pedagogical value, especially when viewed through the lens of critical pedagogy that informs my teaching approach. In this article, I use autoethnographic reflections to describe some of these moments of mutual disruption. I examine how the discussions with students have shifted after the Must Fall movements, linking the philosophy and some of the events of the movements to the ways that students are engaging differently. I argue that these pre-service teachers also hold the potential to disrupt discourses of queerphobia, gender-based violence and HIV in the South African school system. Additionally, I contend that gender and sexuality diversity deserve greater focus in teacher education in order to create critical thinking spaces that can foster reflective capacities in teachers around how they relate to learners who are gender and sexual minorities.